Haemophilus ducreyi Cutaneous Ulcer Strains Are Nearly Identical to Class I Genital Ulcer Strains. - Dharanesh Gangaiah; Kristen M Webb; Tricia L Humphreys; Kate R Fortney; Evelyn Toh; Albert Tai; Samantha S Katz; Allan Pillay; Cheng-Yen Chen; Sally A Roberts; Robert S Munson; Stanley M Spinola (PLoS Neglected Tropical Diseases)
Background Although cutaneous ulcers (CU) in the tropics is frequently attributed to Treponema pallidum subspecies pertenue, the causative agent of yaws, Haemophilus ducreyi has emerged as a major cause of CU in yaws-endemic regions of the South Pacific islands and Africa. H. ducreyi is generally susceptible to macrolides, but CU strains persist after mass drug administration of azithromycin for yaws or trachoma. H. ducreyi also causes genital ulcers (GU) and was thought to be exclusively transmitted by microabrasions that occur during sex. In human volunteers, the GU strain 35000HP does not infect intact skin; wounds are required to initiate infection. These data led to several questions: Are CU strains a new variant of H. ducreyi or did they evolve from GU strains? Do CU strains contain additional genes that could allow them to infect intact skin? Are CU strains susceptible to azithromycin? Methodology/principal findings To address these questions, we performed whole-genome sequencing and antibiotic susceptibility testing of 5 CU strains obtained from Samoa and Vanuatu and 9 archived class I and class II GU strains. Except for single nucleotide polymorphisms, the CU strains were genetically almost identical to the class I strain 35000HP and had no additional genetic content. Phylogenetic analysis showed that class I and class II strains formed two separate clusters and CU strains evolved from class I strains. Class I strains diverged from class II strains ~1.95 million years ago (mya) and CU strains diverged from the class I strain 35000HP ~0.18 mya. CU and GU strains evolved under similar selection pressures. Like 35000HP, the CU strains were highly susceptible to antibiotics, including azithromycin. Conclusions/significance These data suggest that CU strains are derivatives of class I strains that were not recognized until recently. These findings require confirmation by analysis of CU strains from other regions.